Long-term outcomes of CT-guided percutaneous cryoablation of T1a and T1b renal cell carcinoma - Stavros Spiliopoulos; Abdelaziz Marzoug; Hae Ra; Senthil Kumar Arcot Ragupathy (Diagnostic and Interventional Radiology, 2021)

(untitled)
PURPOSEWe aimed to evaluate the long-term outcomes of computed tomography-guided percutaneous cryoablation (PCA) for biopsy-confirmed renal cell carcinoma (RCC).METHODSThis was a single-center, retrospective study investigating all patients treated with PCA between January 2010 and February 2019 for RCC tumors. Primary outcome measures included overall survival (OS), disease-free survival (DFS), progression-free survival (PFS) and cancer-specific survival (CSS). Secondary outcome measures included kidney function, complications, technical success, hospital stay, procedural time, and the identification of factors affecting the primary outcomes.RESULTSFifty-three consecutive patients with 54 lesions (T1a: 49/54; T1b: 5/54) were included. Mean tumor diameter was 28.0±8.5 mm and mean R.E.N.A.L. score was 7.2±2.0. Technical success was 100% (54/54 lesions) after two reinterventions for incomplete ablation. Mean follow-up time was 46.7±28.6 months (range, 3–122 months). Local recurrence was noted in 5 patients (9.2%). According to Kaplan-Meyer analysis, OS was 98.2%, 94.2%, 71.2%, and 58.2% at 1, 3, 5, and 8 years. One patient (1.9%) died of cancer and CSS was 95.8% at 8 years. DFS was 100.0%, 95.5%, and 88.6%, and PFS was 100%, 94.3%, and 91.0%, at 1, 2, and 5 years. Clavien–Dindo grade II complication rate was 7.8% (5/64 procedures). There were no complications classified as grade III or greater. Mean creatinine increase was 7.1±6.3 μm/L (p = 0.31). No patient advanced to dialysis during follow up. Mean procedural time was 163±45 min. Median hospital stay was 2.0 days (IQR, 1–2.5 days). Diabetes was the only independent predictor of decreased OS (hazard ratio 4.3, 95% CI 0.043–0.914; p = 0.038).CONCLUSIONPCA for stage T1a and T1b RCC provides favorable long-term oncological and renal function preservation outcomes, with acceptable complication rates.